Phosphate Homeostasis, Inflammation and the Regulation of FGF-23 - Florian Lang; Christina Leibrock; Aleksandra A. Pandyra; Christos Stournaras; Carsten A. Wagner; Michael Föller (Karger Publishers, 2018)
Fibroblast growth factor 23 (FGF23) is released primarily from osteoblasts/osteocytes in bone. In cooperation with the transmembrane protein Klotho, FGF23 is a powerful inhibitor of 1α 25OH Vitamin D Hydroxylase (Cyp27b1) and thus of the formation of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). As 1,25(OH)2D3 up-regulates intestinal calcium and phosphate absorption, the downregulation of 1,25(OH)2D3 synthesis counteracts phosphate excess and tissue calcification. FGF23 also directly inhibits renal phosphate reabsorption. Other actions of FGF23 include triggering of cardiac hypertrophy. FGF23 formation and/or release are stimulated by 1,25(OH)2D3, phosphate excess, Ca2+, PTH, leptin, catecholamines, mineralocorticoids, volume depletion, lithium, high fat diet, iron deficiency, TNFα and TGFß2. The stimulating effect of 1,25(OH)2D3 on FGF23 expression is dependent on RAC1/PAK1 induced actin-polymerisation. Intracellular signaling involved in the stimulation of FGF23 release also includes increases in the cytosolic Ca2+ concentration ([Ca2+]i) following intracellular Ca2+ release and store-operated Ca2+ entry (SOCE). SOCE is accomplished by the Ca2+ release-activated calcium channel protein 1 (Orai1) and its stimulator stromal interaction molecule 1 (STIM1). Expression of Orai1, SOCE and FGF23-formation are up-regulated by the proinflammatory transcription factor NFκB. The present brief review describes the cellular mechanisms involved in FGF23 regulation and its sensitivity to both phosphate metabolism and inflammation. The case is made that up-regulation of FGF23 by inflammatory mediators and signaling may amplify inflammation by inhibiting formation of the anti-inflammatory 1,25(OH)2D3.